Estimation of vitamin D level in type 1 diabetic children - Enas H Ahmed Hassan; Yasser A Ahmed; Mostafa A Hassan; Mohamed A Bashir (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Previous studies have shown the relationship between children with type 1 diabetes and vitamin D. To evaluate the level of vitamin D in children with type 1 diabetes and the effect of low vitamin D level on the long-term blood glucose controls reflected by glycated hemoglobin. Patients and methods The study included 20 children who had already been diagnosed as having type 1 diabetes mellitus with vitamin D deficiency and 20 normal nondiabetic children as a control group. Full history taking, clinical examinations, and investigations for all children, including serum 25-hydroxy vitamin D level, were done. Results Vitamin D deficiency was present in ∼85% of children with type 1 diabetes compared with nondiabetic control, who showed good vitamin D level. Conclusion Type 1 diabetic children are associated with low vitamin D level. Perhaps infants supplemented with vitamin D level might be a safe and effective plan for decreasing the risk of type 1 diabetes and also may decrease and improve levels of glucose and glycated hemoglobin levels in type 1 diabetes mellitus.